Meltwater as a source of potentially bioavailable iron to Antarctica waters. Issue 3 (26th January 2017) - Monien, Donata; Monien, Patrick; Brünjes, Robert; Widmer, Tatjana; Kappenberg, Arne; Silva Busso, Adrian A.; Schnetger, Bernhard; Brumsack, Hans-Jürgen
Abstract: Recent rapid retreat of glacial front lines and the loss of land ice along the Antarctic margins may play an important role in exporting suspended particulate matter (SPM) potentially rich in bioavailable (defined as ascorbate leachable) iron (FeA ) to coastal areas of the Southern Ocean. Sediment ablation is an additional source of iron for this high-nutrient low-chlorophyll region. In Potter Cove, King George Island, meltwater streams discharge up to 18 000 mg l -1 (average 283 mg l -1 ) of slightly weathered, finely ground bedrock particles into coastal waters during the summer. Approximately 15% of this SPM is exported within a low-salinity surface plume into Bransfield Strait. Based on our data, an estimated 12 mg m -2 yr -1 of FeA is exported from the South Shetland Island land surface (ice-free and subglacial areas) to the surrounding coastal waters. Extrapolated to an area of 2.5x10 4 km 2, this FeA input is comparable to the contribution from icebergs and c. 240-fold higher than aeolian input via dust. An observed rise in local sediment accumulation rates suggests that glacial erosion has been increasing over recent decades and that (sub-)glacially derived SPM is becoming more important as a source of iron to the Southern Ocean.